Intravascular lithotripsy assisted chronic total occlusion revascularization with reverse controlled antegrade retrograde tracking. Issue 7 (6th March 2019) - Yeoh, Julian; Hill, Jonathan; Spratt, James C.
Abstract: Advances in percutaneous coronary intervention (PCI) techniques in chronic total occlusion (CTO) procedures have improved the success of this procedure. CTO PCI via the retrograde approach are facilitated most frequently by reverse controlled antegrade/retrograde tracking (R‐CART). This aims to create a communication between the proximal and distal lumens, which may be achieved between intimal and subintimal spaces. In patients with calcified coronary vessels, creating sufficient disruptions to connect these spaces can be challenging. Intravascular lithotripsy (IVL) has become a useful tool to modify intracoronary calcification for stent deployment and expansion. This case demonstrates the utility of IVL in facilitating connection in R‐CART to complete the CTO PCI where heavy calcification was present at the site of chronic occlusion.